2018
DOI: 10.1016/j.jpeds.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive and Health Correlates of Overweight and Obesity among Ten-Year-Old Children Born Extremely Preterm

Abstract: Among children born extremely preterm, an elevated BMI, compared with normal or low BMI, is not associated with a difference in neurocognitive function. However, asthma, fair/poor general health, and decreased physical function were more prevalent among study participants with obesity, and attention-deficit/hyperactivity disorder and individualized education plan were less prevalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…Further studies are warranted to continue investigating these suggested links. The lack of impact of ISO-BMI and SGA in our sample is consistent with previous studies (23,25). Here, height is tentatively proposed as an important factor in relation to neurodevelopmental outcome in mainly able children born PT at school age.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Further studies are warranted to continue investigating these suggested links. The lack of impact of ISO-BMI and SGA in our sample is consistent with previous studies (23,25). Here, height is tentatively proposed as an important factor in relation to neurodevelopmental outcome in mainly able children born PT at school age.…”
Section: Discussionsupporting
confidence: 92%
“…Further, birth immaturity may also involve growth restriction in developing children, with potential impact on cognitive and behavioral functioning. Postnatal growth (i.e., weight, height, and body mass index, BMI) in children born PT has been associated with both short- and long-term neurodevelopmental outcome ( 22 25 ). A fast growth gain during infancy has been found related to better cognitive outcomes in later childhood, although it comes with a risk of developing obesity ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study in which the KC and supine positions were compared, the gastric residual volume was lower in those fed in KC than in those fed in supine position (Valizadeh, Hosseini, Jafarabadi, & Mohebbi, 2015). Gastric residual volumes are frequently measured to guide the advancement of enteral feeding; however; there is no clear evidence to justify their usefulness in either improving feeding intolerance or preventing necrotizing enterocolitis (Linthavong et al, 2018). Although there are no studies on the effect of gastric residual volume on comfort, increased gastric residual volume induced abdominal distension is predicted to adversely affect comfort.…”
Section: Introductionmentioning
confidence: 99%